Geografija - prostorski koncept in planiranje - Černe, Andrej (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 1997)
The purpose of this paper is to present certain considerations about geography as a science, its conceptual and spatial plans, the geographical aspect, and the geographical methodology which form a basis for an active role of geography in the various fields of planning.
Keywords: družbena geografija; human geography; metodologija; prostorsko planiranje; regionalno planiranje; spatial planning